2021
DOI: 10.1016/j.aninu.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acids–essential oils blend and oat fiber combination on broiler chicken growth performance, blood parameters, and intestinal health

Abstract: This study evaluated the effect of organic acids-essential oils blend with or without oat hulls (OH) on growth performance, organ weights, blood parameters, gut morphology, microbiota, and short-chain fatty acids (SCFA) in broiler chickens. Day-old broiler chickens were randomly allocated to 4 dietary treatments consisting of 1) a corn-soybean meal-wheat based diet (BAS), 2) BAS + 0.05% bacitracin methylene disalicylate (BMD), 3) BAS + protected organic acids-essential oils at 300 g/1,000 kg of feed (OE), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 108 publications
4
18
0
1
Order By: Relevance
“…The positive effect of EO on ceca SCFA concentration could be related to the capacity of their phytogenic formulations to enhance bacteria proliferation in the lower gut. Several variable factors that potentially influence SCFA concentrations in broiler chickens, including the microbiota composition, bird age, and the amount and type of available fermentable substrates, explain the observed results in this study [ 23 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 86%
“…The positive effect of EO on ceca SCFA concentration could be related to the capacity of their phytogenic formulations to enhance bacteria proliferation in the lower gut. Several variable factors that potentially influence SCFA concentrations in broiler chickens, including the microbiota composition, bird age, and the amount and type of available fermentable substrates, explain the observed results in this study [ 23 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 86%
“…With the coming of the antibiotic-free feeding era, it is extremely urgent to seek effective and pollution-free alternatives as to antibiotics in animal production ( Thacker, 2013 ; Mehdi et al, 2018 ; Lopez-Galvez et al, 2021 ). Organic acids have been commonly applied to animal feed due to their beneficial effects, such as antimicrobial activity, enhancement of nutrient digestibility, and improvement of intestinal morphology ( Suiryanrayna and Ramana, 2015 ; Adewole et al, 2021 ). As a renewable organic acid, IA has received increasing attention from researchers due to its multiple biological functions ( Hooftman and O'Neill, 2019 ; Zhu, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the growth performance of broiler chickens, previous studies showed that dietary supplementation with 3% citric acid or 0.1% organic acid blends (combinations of citric acid, lactic acid, formic acid, acetic acid, propionic acid, sodium butyrate, and phosphoric acid) increased the ADG and ADFI of broilers and reduced the F/G ratio ( Khosravinia et al, 2015 ; Sabour et al, 2019 ; Emili et al, 2021 ); however, this was not always the case. Several studies also revealed that the addition of 0.03% citric acid blends (combinations of citric acid, fumaric acid, sorbic acid, and malic acid) to diets did not affect weight gain, FI, or F/G ( Yang et al, 2019 ; Adewole et al, 2021 ). Differences in results among these studies may be related to the source, dose, and type of organic acids used in the broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…The in ovo technology has been recognized to be a means to stimulate the development of the embryonic gastrointestinal tract (GIT) [ 44 ]. The potential of the active ingredients in the EO blend to stimulate the secretion of endogenous digestive enzymes while also ensuring a balanced gut microbial diversity could also have contributed to the observed effect [ 144 , 145 , 146 ]. The antimicrobial, anti-inflammatory, and antioxidant properties of the supplied EO blend also play an important role in gut morphometric development [ 146 , 147 ].…”
Section: Discussionmentioning
confidence: 99%